O gênero do discurso carta como ferramenta didático-pedagógica para o ensino de Língua Portuguesa - Figueiredo, João Paulo Barbosa de (2013)
In this thesis we address a letter written by Padre Antonio Vieira, which has motivated us to develop good practices of reading and writing in public schools. The proposed approach is not restricted to observe only grammatical aspects, but intend to examine the discursive units responsible for configuring, based on interdiscourse, the diplomatic discourse, written by one of the greatest orators of the seventeenth century. This theme has a special academic and social relevance due to the honorable representation of Vieira in the Portuguese Letters, who made vast correspondence, besides his sermon prose, which makes his work worthy of being researched today, in contemporary times. Moreover, given the wealth of information contained in his epistler, the language of the seventeenth century is an exemplary source of the linguistic repertoire of the students who came into contact with the selected letter. Working with speech genres has become increasingly present in state schools. However, its emphasis focuses on the text, which sometimes can relegate to second place important aspects of the discourse. Accordingly, we tried to analyze our corpus, composed of ten letters written by the students and the standard letter produced by Vieira, including the contributions of Bakhtin, one of the first theorists to deal with the notion of gender perspective in the discourse, and Maingueneau, a researcher in Discourse Analysis, whose productivity is very expressive nowadays. To accomplish the analysis, we used the categories of gender discourse in Bakhtin's approach and the scenes of enunciation, which includes: encompassing scene, generic scene and scenography, from the perspective of Maingueneau. The theoretical framework allowed us to reveal that the recurrent features of discourse genre of the letter can be recognized and used by the students in other productions. Furthermore, the notion of scenography has become very useful to understand the conditions of production of the discourses of Vieira and his students, with regard to gender analysis. The proposed methodology for the teaching of portuguese language can support the task of other public school teachers